Seasonal and decadal variations in absorption properties of phytoplankton and non-algal particulate matter in three oceanic regimes of the Northwest Atlantic - Devred, Emmanuel; Perry, Tim; Massicotte, Philippe (Frontiers in Marine Science, 2022)
Seasonal and inter-annual absorption properties of phytoplankton and non-algal particulate matter were studied in relation to phytoplankton biomass, as indexed by chlorophyll-a concentration, and presence of diatoms, as indexed by fucoxanthin concentration, using a 20-year time series of in situ data collected in the Northwest Atlantic. We found significant differences in the spatiotemporal variations of the bio-optical properties for three oceanic regimes: mesotrophic (Scotian Shelf), oligotrophic (Northwest Atlantic Basin, NAB), and subartic (Labrador Sea). The Scotian Shelf and NAB exhibited similar phenology with the spring and autumn blooms associated with low phytoplankton specific absorption, while only relatively high fucoxanthin concentration occurred in spring. The NAB showed a smaller seasonal variation than the Scotian Shelf in agreement with its oceanic conditions. The Labrador Sea showed a single phytoplankton bloom in spring followed by a continuous decrease in biomass the rest of the year. The relationship between phytoplankton absorption coefficient at 443 nm and chlorophyll-a concentration was consistent with other studies with coefficients that were region-dependent. Absorption by non-algal particulate matter remained between 5% and 60% of phytoplankton absorption with a mean of 15%. The slope of the non-algal particulate absorption varied with seasons and regions and appeared to depend on the trophic status with high values (i.e., up to 0.04) occurring during bloom conditions. We also introduced a new index, the phytoplankton apparent absorption wavelength (PAAW), a wavelength-weighted sum of absorption expressed in nanometers that provides information on the phytoplankton biomass and assemblage in a simple manner. Time series analysis of the PAAW revealed a decrease of this property in spring on the Scotian Shelf, NAB, and Labrador Sea and an increase in autumn on the Scotian Shelf and NAB, suggesting a shift in these ecosystems.